1981
DOI: 10.3109/00365528109181984
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Intramural Nerves in the Pathogenesis of Cholera Toxin-induced Intestinal Secretion

Abstract: Intestinal secretion was produced in anesthetized cats and rats by exposing isolated intestinal segments to cholera enterotoxin. Giving, for example, tetrodotoxin, a nerve-conduction-blocking agent, or adding lidocaine, a local anesthetic agent, to the solution in the intestinal segments markedly inhibited the rate of choleraic secretion, and in most experiments a net absorption of fluid was observed. The results suggest that intramural nervous mechanisms are involved in the pathogenesis of choleraic secretion. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 18 publications
6
64
0
Order By: Relevance
“…These observations indicate that the enteric circuitry controlling CCK-RP secretion is present in the submucous not myenteric plexus. Similar studies with intestinal perfusion of lidocaine and intraarterial infusion of tetrodotoxin showed that the submucous nervous system is involved in mediating intestinal secretion induced by cholera toxin (29) or bile salts (30).…”
Section: Discussionmentioning
confidence: 65%
“…These observations indicate that the enteric circuitry controlling CCK-RP secretion is present in the submucous not myenteric plexus. Similar studies with intestinal perfusion of lidocaine and intraarterial infusion of tetrodotoxin showed that the submucous nervous system is involved in mediating intestinal secretion induced by cholera toxin (29) or bile salts (30).…”
Section: Discussionmentioning
confidence: 65%
“…CT stimulation of Cl -secretion is considerably more complicated than solely its interaction with intestinal epithelial cells because tetrodotoxin (TTX; an inhibitor of neurotransmission) blocks approximately 50% of CT-stimulated fluid secretion, indicating that CT interacts with the enteric nervous system (ENS) (84). Present concepts indicate that CT induces the ENS to release vasoactive intestinal peptide (VIP), which activates adenylate cyclase and increases mucosal cAMP in intestinal epithelial cells.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Present concepts indicate that CT induces the ENS to release vasoactive intestinal peptide (VIP), which activates adenylate cyclase and increases mucosal cAMP in intestinal epithelial cells. Thus, the ENS, as well as several lamina propria cells including myofibroblasts, have been identified as critical in the interaction of toxins with intestinal epithelial cells and the production of intestinal secretion or, in other cases, inflammation (84)(85)(86). Even rotaviruses, which invade and damage intestinal villous cells, release a novel Ca 2+ -dependent enterotoxin, NSP4, which inhibits brush border disaccharidases and glucose-stimulated Na + absorption (87,88).…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, it had no effect on 'intestinal net fluid transport' in the absence of CT (basal fluid absorption?) in the rat deprived of its food for just 12 h before use (Cassuto, Jodal, Tuttle & Lundgren, 1981). These measurements in rats were made using the gravimetric isolated loop technique that we employed.…”
Section: Chemicalsmentioning
confidence: 99%